Language teachers’ ICT up-take in a single university in the developing country Kazakhstan - Akmarzhan A. Nogaibayeva; Gulzhaina K. Kassymova; Sulis Triyono; Binar Winantaka (LPMPP Universitas Negeri Yogyakarta, 2023)
This article reports on the findings of what we consider to be the first study of its sort on the use of ICT (information and communication technology) in English, Russian, and Kazakh language teachers in a single university in Kazakhstan. Participants include 111 (English, Russian, Kazakh) instructors from three departments. The study’s goal was to look at these language teachers’ ICT use and the elements that influence their use of ICT as a teaching tool. The following study issues were addressed using questionnaires and follow-up semi-structured interviews: What is the present state of information and communication technology (ICT) use among a group of language teachers in a single university in Kazakhstan? What ICT skills do language teachers have, and what training is available? What are factors that encourage/discourage the use of ICT in their teaching and learning? Findings support the idea that most teachers have owned their own computers to be used in the class and most teachers in the study had adequate skills. However, computer use is mainly limited to PowerPoint presentations but there are patterns of creative ICT use. Positive factors affecting ICT use include willingness to ICT use in teaching and the benefits to both teachers and learners, while negative factors include inadequate professional support, poor training, and the need for a more holistic approach to ICT integration. The conclusions are that ICT is acknowledged as essential and advantageous to language learners as well as teachers from a teaching perspective and that teachers require additional training: to provide training opportunities at the institutional level to support their ICT use and to help language teachers better understand the pedagogy of technology use and incorporate ICT into their instruction. The authors propose that this type of support might be offered through professional development activities that are tailored to the context of language teaching and learning.